Performance of the 2017 and 2010 Revised McDonald Criteria in Predicting MS Diagnosis After a Clinically Isolated Syndrome: A MAGNIMS Study. (4th January 2022) - Filippi, Massimo; Preziosa, Paolo; Meani, Alessandro; Dalla Costa, Gloria; Mesaros, Sarlota; Drulovic, Jelena; Ivanovic, Jovana; Rovira, Alex; Tintorè, Mar; Montalban, Xavier; Ciccarelli, Olga; Brownlee, Wallace; et al.
Abstract : Background and Objectives: To compare the performance of the 2017 revisions to the McDonald criteria with the 2010 McDonald criteria in establishing multiple sclerosis (MS) diagnosis and predicting prognosis in patients with clinically isolated syndrome (CIS) suggestive of MS. Methods: CSF examination and brain and spinal cord MRI obtained ≤5 months from CIS onset and a follow-up brain MRI acquired within 15 months from CIS onset were evaluated in 785 patients with CIS from 9 European centers. Date of second clinical attack and of reaching Expanded Disability Status Scale score (EDSS) ≥3.0, if they occurred, were also collected. Performance of the 2017 and 2010 McDonald criteria for dissemination in space (DIS), dissemination in time (DIT) (including oligoclonal bands assessment), and DIS plus DIT for predicting a second clinical attack (clinically definite MS [CDMS]) and EDSS ≥3.0 at follow-up was evaluated. Time to MS diagnosis for the different criteria was also estimated. Results: At follow-up (median 69.1 months), 406/785 patients with CIS developed CDMS. At 36 months, the 2017 DIS plus DIT criteria had higher sensitivity (0.83 vs 0.66), lower specificity (0.39 vs 0.60), and similar area under the curve values (0.61 vs 0.63). Median time to MS diagnosis was shorter with the 2017 vs the 2010 or CDMS criteria (2017 revision, 3.2; 2010 revision, 13.0; CDMS, 58.5 months). The 2 sets of criteria similarly predicted EDSS ≥3.0 milestone. Three periventricular lesions improved specificity in patients ≥45 years. Discussion: The 2017 McDonald criteria showed higher sensitivity, lower specificity, and similar accuracy in predicting CDMS compared to 2010 McDonald criteria, while shortening time to diagnosis of MS. Classification of Evidence: This study provides Class II evidence that the 2017 McDonald Criteria more accurately distinguish CDMS in patients early after a CIS when compared to the 2010 McDonald criteria.